2013
DOI: 10.24252/bio.v1i1.442
|View full text |Cite
|
Sign up to set email alerts
|

Uji Ketahanan Salinitas Beberapa Varietas Jagung (Zea mays L.) Dengan Menggunakan Agen Seleksi NaCl

Abstract: This study aims to determine the concentration of NaCl which can be used as maize resistance limit to salinity and to obtain varieties that are tolerant to salinity. This research was conducted in the form of an experiment with randomized design factorial using two factors in the group. As the first factor is the variety of Arjuna, Sukmaraga, Bhishma, Gumarang, Heroine Yellow, Pacakka, Anoman-1, and LAMURU. The second factor is the concentration of NaCl with 0 g L -1 , 3 g L -1 , 4 g L -1 , and 5 g L -1 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
9
0
8
Order By: Relevance
“…Marwanto et al (2009) reported that thesalinity soil in Indramayu district was varied from 0.03-12.91 dS/m and it was classified as saline as effect of sea intrusion. Dachlan (2013) reported that in South Sulawesi, soil salinity has become important problem, especially in coastal areas such as in Districts of Jeneponto, Pangkep, Bantaeng, Selayar, and Barru. Moreover, recent global climate change has made this situation much worse.…”
Section: Introductionmentioning
confidence: 99%
“…Marwanto et al (2009) reported that thesalinity soil in Indramayu district was varied from 0.03-12.91 dS/m and it was classified as saline as effect of sea intrusion. Dachlan (2013) reported that in South Sulawesi, soil salinity has become important problem, especially in coastal areas such as in Districts of Jeneponto, Pangkep, Bantaeng, Selayar, and Barru. Moreover, recent global climate change has made this situation much worse.…”
Section: Introductionmentioning
confidence: 99%
“…Plant quantitative characters are influenced by many genes and are heavily influenced by the environment. [20] state that genetic and environmental influences are factors that cause differences in the appearance of each plant (phenotype).…”
Section: B Discussionmentioning
confidence: 99%
“…Media tanam yang digunakan pada penelitian ini yaitu campuran tanah, pasir dan pupuk kandang sapi dengan perbandingan volume 2:1:1 (Dachlan et al 2013). Campuran media tanam tanah, pasir dan pupuk kandang sapi di masukkan ke dalam polibag dengan ukuran 8 kg.…”
Section: Metode Penelitianunclassified